The Program Development to Enhance Academic Leadership of administrators in Surin Secondary Educational Service Area Office - Baibua, Anongpat; Ruangmontri, Karn (Journal of Graduate MCU KhonKaen Campus, 2026)
This research aimed to (1) study the current conditions, desirable conditions, and needs regarding the academic leadership of school administrators under the Surin Secondary Educational Service Area Office; and (2) develop and evaluate a program to enhance the academic leadership of these administrators. The sample consisted of 341 participants, including school administrators and teachers under the Surin Secondary Educational Service Area Office. The sample size was determined using Krejcie and Morgan’s table, and stratified random sampling was used to obtain the participants. The key informant group included 3 exemplary school administrators and 5 experts. The research instruments were questionnaires, interviews, and evaluation forms. The statistics used for data analysis included basic statistics: frequency, percentage, mean, standard deviation, and the needs index (PNI). The research findings revealed that: 1. The academic leadership of school administrators under the Surin Secondary Educational Service Area Office, in terms of current conditions, was at a moderate level overall. The desirable conditions were at a high level. The needs index was 0.34. The priority order of needs was found to be: First: learning management administration, Second: curriculum administration and development, Third: collaborative supervision and development, Fourth: goal setting and planning. 2. The program developed to enhance the academic leadership of school administrators under the Surin Secondary Educational Service Area Office was based on the 70:20:10 Learning Model. This model was used to develop administrators by strengthening their academic leadership through three approaches: training, learning from practice, and workshops. The program consisted of six components: principles, objectives, target group, content, implementation, and evaluation. Four learning modules were designed: Module 1: goal setting and planning Module 2: curriculum administration and development Module 3: learning management administration Module 4: collaborative supervision and development. The total duration of the program was 300 hours (approximately one semester). The program evaluation by experts showed that the program was highly appropriate and highly feasible